O Pensamento Lean na gestão de processos de mobilidade acadêmica nacional em uma instituição de ensino superior pública: um estudo de caso - Petrilli, Fernando Moura Fabbri (Universidade Federal de São Carlos, 2018)
In the Brazilian Universities, one of the great possibilities of complementary formation with strong academic, cultural and social enrichment for students, teachers and technical-administrative is the participation in programs of academic mobility. In order for academic mobility to take place, a series of actions are necessary to ensure the success of its proposal, from the dissemination of opportunities to the return of the exchange student to his home institution. "Lean Thinking", has its origins in the automotive industry and has promoted a revolution in industrial management models by directing its actions to the customer's interests, through continuous process improvements, elimination of waste and focus on total quality. As a result, the successes achieved by this management method have been adapted to improve processes in other sectors, such as administrative services, including those related to public administration, and the Lean Office has emerged. In this context, the present work aims to present a case study about the management of processes directed to Academic Mobility in a Federal Institution of Higher Education by the methodology of mapping SIPOC processes. The results obtained demonstrate the existence of operational waste points in the actions carried out and present suggestions for improvements in the processes so that the activities are more objective and agile to all involved
Lean thinking on management of national academic mobility processes in a public higher education institution: a case study
Keywords: Mobilidade acadêmica; Gestão de processos; Academic mobility; Process management; Lean Office; CIENCIAS SOCIAIS APLICADAS::ADMINISTRACAO::ADMINISTRACAO PUBLICA::ORGANIZACOES PUBLICAS; CIENCIAS SOCIAIS APLICADAS::ADMINISTRACAO::ADMINISTRACAO PUBLICA